Patient-Active Control of a Powered Exoskeleton Targeting Upper Limb Rehabilitation Training - Wu, Qingcong; Wang, Xingsong; Chen, Bai; Wu, Hongtao (Frontiers in Neurology, 2018)
Robot-assisted therapy affords effective advantages to the rehabilitation training of patients with motion impairment problems. To meet the challenge of integrating the active participation of patient into robotic training, this study presents an admittance-based patient-active control scheme for real-time intention-driven control of a powered upper limb exoskeleton. A comprehensive overview is proposed to introduce the major mechanical structure and real-time control system of the developed therapeutic robot, which provides seven actuated degrees of freedom and achieves natural ranges of human arm movement. Moreover, the dynamic characteristics of the human-exoskeleton system are studied via Lagrangian method. Then, the patient-active control strategy consisting of an admittance module and a virtual environment module is developed to regulate the robot configurations and interaction forces during rehabilitation training. The audiovisual game-like interface is integrated into the therapeutic system to encourage the voluntary efforts of patient and recover the neural plasticity of brain. Further experimental investigation, involving position tracking experiment, free arm training experiment, and virtual airplane-game operation experiment, are conducted by three healthy subjects and eight hemiplegic patients with different motor abilities. Experimental results validate the feasibility of the proposed scheme in providing patient-active rehabilitation training.